Halal Lifestyle and Maqāṣid al-Syarī'ah: A Legal Reconstruction of Family Well-being in Contemporary Muslim Society (Comparative Study of Indonesia and Malaysia) - Andi Sumardin; Ardi Ardi; M. Hasibuddin; Bishri Abdul Karim (Bulletin of Community Engagement, 2026)
This research reconstructs the relationship between halal lifestyle and maqāṣid al-syarī'ah in developing a sustainable model of Muslim family well-being through a comparative study of Indonesia and Malaysia. The study addresses a three-layered research gap: halal scholarship examines halal lifestyle primarily as consumer behaviour; Islamic legal scholarship elaborates maqāṣid largely at a theoretical-hermeneutical level; and comparative policy research rarely links halal governance with family well-being. Employing a qualitative-normative design, the study combines a PRISMA-guided systematic literature review of 32 academic sources retrieved from Scopus and Web of Science (2015–2025), together with 11 primary legal-policy documents, analysed thematically and compared across six explicit dimensions: legal framework, governance architecture, certification regime, integration with family policy, maqāṣid orientation, and halal literacy with well-being monitoring. The findings show that, when internalised maqāṣidīcally, the halal lifestyle strengthens family well-being across spiritual, intellectual, social and economic domains. Indonesia's halal assurance system (Law No. 33/2014, Government Regulation No. 39/2021, mandatory since 18 October 2024) remains legal-formal and product-centred, whereas Malaysia's Halal Industry Master Plan 2030 and national family policy articulate a more integrative model. The study is limited to conceptual and policy analysis without large-scale quantitative data and to a two-country comparison. It proposes the Maqāṣid-based Halal Family Well-being Framework and extends Jasser Auda's systems approach by positioning the family as the meso-level unit through which openness, multidimensionality and purposefulness are institutionally realised in halal governance.